Time to death and its predictors among neonates with seizure in North West Ethiopia - Tamene Fetene Terefe; Tamiru Alene; Manay Ayalneh; Nigatu Dessalegn; Yosef Aragaw Gonete; Baye Tsegaye Amlak; Fisha Alebel GebreEyesus; Alemayehu Wondie; Melaku Bimerew (Scientific Reports)
Abstract Neonatal seizures were associated with significant rates of mortality; in which about one-third of the neonates with seizure ending up with death. Despite this, the time to death and its predictors among neonates with seizure has not been investigated; especially in Ethiopia. To determine the time to death and its predictors among neonates with seizure in public hospitals of Awi zone, Northwest Ethiopia. A multicenter prospective follow-up study was conducted in public hospitals of Awi zone on 263 neonates with seizure. Descriptive statistics, Kaplan–Meier curve, Nelson–Aalen curves, and log-rank tests were employed to describe the time to death and to assess the risk of mortality among different covariates. The Cox proportional hazards model was used to identify the predictors of time to death. AHR with 95% CI was used to identify significant predictor variables, and a statistical significance was declared at p-value < 0.05. A total of 263 neonates with seizure were followed for a total of 1334.3 person-days, and the incidence of mortality was found to be 22.5 per 1000 person-day observations (95% CI = 14.0–29.6). The median time to death was 3 days (IQR = 2–5 days). Birth trauma (AHR = 3.9, 95% CI = 1.5–10.6), neonatal sepsis (AHR = 3.4, 95% CI = 1.1–10.8), hypoglycemia (AHR = 3.2, 95% CI = 1.1–9.3), and tonic type seizure (AHR = 4.5, 95% CI = 1.3–15.6) were statistically significant predictors of early mortality in neonates with seizure. This study revealed that the incidence of in-hospital mortality among neonates with seizure to be high and the median time to death to be short; and the predictors of early mortality were identified. Early detection and appropriate management of neonates having birth trauma, sepsis, and hypoglycemia might be helpful.